Climate Change and Investment Efficiency in Egyptian Firms: The Moderating Effect of Cash Holding - Azer, Rania Hani Ramzi (المجلة العلمية للدراسات والبحوث المالية والتجارية: علمية محكمة., 2025)
The main objective of this study is to investigate the impact of climate change on investment efficiency in light of the presence of the cash holding as a moderator variable affecting this relationship. the study methodology relies on the content analysis approach by examining and analyzing the financial reports published for a sample consisting of (37) firms listed at the Egyptian stock exchange (EGX) with a total of 259 observations from 2015 to 2021 the research hypotheses were tested using the panel corrected standard errors (PCSE) method and the feasible generalized least squares (FGLS) method. the results of the study concluded that climate change has a negative effect on the investment efficiency in the Egyptian listed firms. also, Egyptian firms with a high level of CH have a tendency to invest at a higher rate. in addition to, cash holdings in Egyptian listed firms support the negative relationship between climate change and investment efficiency. based on this results, Egyptians firms should cash holding as a cushion against climate change risks, support liquidity, overcome financial distress risk, lower the cost of capital, increase future investment opportunities and reduce uncertainty. additionally, policymakers, regulators at the EGX and financial regulatory authority need to realize the importance of climate change and increase the support for firms that adopt environmentally conscious business practices such as the conservation of natural resources, the production of alternative energy sources and the implementation of clean air and water projects in Egyptian listed firms in accordance with Egypt’s vision 2030. يتمثل الهدف الرئيس لهذه الدراسة في التحقق من تأثير تغير المناخ على كفاءة الاستثمار في ظل وجود الاحتفاظ بالنقدية كمتغير مؤثر على هذه العلاقة. وتعتمد منهجية الدراسة على أسلوب تحليل المحتوى وذلك بفحص وتحليل التقارير المالية المنشورة لعينة مكونة من (۳۷) شركة مدرجة في البورصة المصرية (EGX) بإجمالي ٢٥٩ ملاحظة من عام ۲۰۱٥ إلى عام ٢٠٢١. وتم اختبار فرضيات البحث باستخدام طريقة الأخطاء المعيارية المصححة (PCSE) panel corrected standard errors وطريقة المربعات الصغرى المعممة (FGLS) feasible generalized least squares. وخلصت نتائج الدراسة إلى أن تغير المناخ له تأثير سلبي على كفاءة الاستثمار في الشركات المصرية المدرجة. كما أن الشركات المصرية ذات المستوى المرتفع من الحيازة النقدية لديها ميل للاستثمار بمعدل أعلى. بالإضافة إلى ذلك، فإن الحيازات النقدية في الشركات المصرية المدرجة تدعم العلاقة السلبية بين تغير المناخ وكفاءة الاستثمار. واستنادا إلى ذلك توصى الدراسة بضرورة اهتمام الشركات المصرية بالاحتفاظ بالنقدية كوسيلة للوقاية من مخاطر تغير المناخ، ودعم السيولة، والتغلب على مخاطر الضائقة المالية، وخفض تكلفة رأس المال، وزيادة فرص الاستثمار المستقبلية والحد من عدم اليقين. بالإضافة إلى ذلك، ضرورة إدراك صناع السياسات والجهات التنظيمية في البورصة المصرية وهيئة الرقابة المالية أهمية تغير المناخ وزيادة الدعم للشركات التي تتبنى ممارسات تجارية واعية بيئيا مثل الحفاظ على الموارد الطبيعية، وإنتاج مصادر الطاقة البديلة وتنفيذ مشاريع الهواء النظيف والمياه في الشركات المصرية المدرجة وفقا لرؤية مصر ۲۰۳۰.